Pengaruh Kecerdasan Intelektual dan Kecerdasan Spiritual terhadap Kualitas Audit pada Kantor Inspektorat Aceh - Surna Lastri; Agus Susanto (SI-MEN, 2019)
This research is empirical in which the goal to be achieved in this research is to know the influence of intellectual intelligence and spiritual intelligence on audit quality at the Office of the Inspectorate of Aceh, either simultaneously or partially. The population in this study is the Auditor who works at the Inspectorate Office of Aceh. The number of population taken is 83 people. Samples taken in the study were 83 people. So the sampling method used is a census because it involves the entire population to be a research respondent. Based on the results of research based on simultaneous testing obtained Fcount value of 31.991, while Ftabel at significance level µ = 5% is equal to 3,110. It shows that Fcount> Ftable, with a probability level of 0.000. Thus the results of this calculation can be taken a decision that accept alternative hypothesis and reject the null hypothesis, meaning that the intellectual intelligence (X1), and spiritual intelligence (X2), together significantly affect the quality of audit at the Office of the Inspectorate Aceh. While the result of partial test of the variable having the highest regression coefficient value (most dominant), is intellectual intelligence (X1) has dominant influence on audit quality, with coefficient value 0,200, it shows that intellectual intelligence run by Office Inspektorat Aceh in perform audit actions are appropriate, so that affect the improvement of audit quality.